Vascular Function Long Term After Kawasaki Disease: Another Piece of the Puzzle? - Pinto, MF (2017)
BACKGROUND: Kawasaki disease is an acute systemic vasculitis. Cardiac complications are frequent and include endothelial dysfunction in patients with coronary anomalies. Thus far, endothelial dysfunction in patients with no coronary lesions is poorly understood. Our aim was to access the vascular function in adolescents and young adults long term after Kawasaki disease, but without coronary aneurysms or any other cardiac risk factors. METHODS: We carried out a single-centre prospective study in a Portuguese population. We evaluated two groups of subjects: (1) Kawasaki disease patients over 11 years of age, diagnosed >5 years ago, with no coronary lesions or any other risk factors for cardiovascular disease; (2) control group of individuals without cardiovascular risk factors. Patients and controls were clinically assessed. Endo-PAT and carotid intima-media thickness assessment were performed to determine vascular function. RESULTS: In total, 43 Kawasaki disease patients were assessed and compared with 43 controls. Kawasaki disease patients presented a decreased reactive hyperaemia index compared with controls (1.59±0.45 versus 1.98±0.41; p<0.001). Augmentation index was similar in both groups (-4.5±7 versus -5±9%; p 0.6). The mean carotid intima-media thickness was not significantly increased in the Kawasaki disease group. There were no statistically significant changes with regard to laboratory data. CONCLUSIONS: Children with Kawasaki disease may have long-term sequelae, even when there is no discernible coronary artery involvement in the acute stage of the disease. Further research is needed to assess whether known strategies to improve endothelial function would bring potential benefits to Kawasaki disease patients.